1989
DOI: 10.1073/pnas.86.18.7159
|View full text |Cite
|
Sign up to set email alerts
|

Specific, major histocompatibility complex-unrestricted recognition of tumor-associated mucins by human cytotoxic T cells.

Abstract: We have previously reported the establishment of cytotoxic T-cell lines, from pancreatic cancer patients, by continuously stimulating tumor-draining lymph node cells with allogeneic pancreatic tumor cell lines. After the preliminary characterization of their phenotype and tumor specificity, detailed studies performed with one of the cell lines, W.D., show that it recognizes a specific antigen, a large and heavily glycosylated mucin molecule, expressed on pancreatic and breast tumors and tumor cell lines. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
208
2
3

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(216 citation statements)
references
References 21 publications
3
208
2
3
Order By: Relevance
“…In humans, both unrestricted and MHC class I-restricted MUC1-specific CTLs have been reported (8,25); however, we have only detected MHC class I-restricted CTLs in MET mice. It must be realized that the situation in vivo may be quite different from that in vitro.…”
Section: Figurecontrasting
confidence: 50%
See 1 more Smart Citation
“…In humans, both unrestricted and MHC class I-restricted MUC1-specific CTLs have been reported (8,25); however, we have only detected MHC class I-restricted CTLs in MET mice. It must be realized that the situation in vivo may be quite different from that in vitro.…”
Section: Figurecontrasting
confidence: 50%
“…Oligosaccharide structures are shorter and fewer in number, revealing immunodominant peptide sequences in every TR that on normal surfaces would be concealed by glycosylation (7). Underglycosylation of MUC1 reveals peptide epitopes recognized by cytotoxic T cells that can kill tumor cells expressing this form of MUC1 (8,9).…”
mentioning
confidence: 99%
“…Increased expression of underglycosylated MUC1 has been documented in adenomatous polyps as well as colorectal adenocarcinomas [11][12][13]. Underglycosylation of MUC1 leads to exposure of cryptic epitopes that can be recognized by cytotoxic T lymphocytes (CTL) [14,15]. Although MUC1 is a self protein, immune responses against MUC1, as manifested by the presence of antibodies and CTL, have been reported in some patients with breast, ovarian and colon cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…Underglycosylation of MUC1 leads to exposure of cryptic epitopes that can be recognized by cytotoxic T lymphocytes (CTL) [14,15]. Although MUC1 is a self protein, immune responses against MUC1, as manifested by the presence of antibodies and CTL, have been reported in some patients with breast, ovarian and colon cancer [14]. Furthermore, studies of MUC1-expressing transgenic mice have demonstrated the presence of MUC1-specific CTLs that can kill MUC1-expressing tumor cells in vitro and suppress tumor growth in vivo [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…5 MUC-1, which is expressed on the surface of many malignant cells, contains multiple tandem repeats of the PDTRP epitope. 6 Barnd et al 7 found that PDTRP-specific immune responses could be detected in breast cancer patients, suggesting that PDTRP could serve as an immunogen to induce antitumor immunity. Using somatic transgene immunization (STI), we showed that immune responses to PDTRP could be elicited following PDTRP gene immunization by incorporating PDTRP coding sequence into the complementary domain region 3 (CDR3) of an immunoglobulin heavy chain in a plasmid vector (g1neoPDTRP).…”
Section: Introductionmentioning
confidence: 99%